VALUE ENGINEERING IN CONSTRUCTION OF THE PUBLIC LECTURE BUILDING AND LABORATORY FACULTY OF SOCIAL AND POLITICAL SCIENCES PHASE 2 UPN VETERAN EAST JAVA - Yasinta Nuril Al Mas; Suhariyanto Suhariyanto; Fauzi Akbar Rahmawan (Jurusan Teknik Sipil Politeknik Negeri Malang, 2026)
The construction project of the Public Lecture Building and Laboratory for the Faculty of Social and Political Sciences Phase 2 at UPN “Veteran” East Java aims to support educational and research activities. To improve cost efficiency without compromising the building’s function and quality, the Value Engineering (VE) method was applied. This method is used to evaluate the main functions of a project and to find more economical and efficient alternatives in design, materials, or construction methods. The research was conducted through five VE stages: information, function analysis, idea generation, evaluation, and recommendation. The analysis focused on elements with the highest cost contribution, specifically structural beam work and slab work. The Velue Engineering results showed that the structural beam work could be replaced with a more efficient alternative. For example, Alternative 1 uses bamboo scaffolding with a diameter of 8–10 cm and a length of 4 m, and beam formwork made of 12 mm plywood. This alternative could save up to IDR 116,148,590.99 from the initial project budget. For slab work, the alternative includes using bamboo scaffolding with the same specifications and 12 mm plywood formwork. These alternatives were applied without reducing the building’s quality or function. The implementation of VE has proven effective in supporting decision-making in construction projects, especially for building higher education facilities that require efficiency and sustainability.